Association of Tumor Treating Fields (TTFields) therapy with survival in newly diagnosed glioblastoma: a systematic review and meta-analysis - Ballo, Matthew T; Conlon, Patrick; Lavy-Shahaf, Gitit; Kinzel, Adrian; Vymazal, Josef; Rulseh, Aaron M (Journal of neuro-oncology, 2023)
PURPOSE: Tumor Treating Fields (TTFields) therapy, an electric field-based cancer treatment, became FDA-approved for patients with newly diagnosed glioblastoma (GBM) in 2015 based on the randomized controlled EF-14 study. Subsequent approvals worldwide and increased adoption over time have raised the question of whether a consistent survival benefit has been observed in the real-world setting, and whether device usage has played a role. METHODS: We conducted a literature search to identify clinical studies evaluating overall survival (OS) in TTFields-treated patients. Comparative and single-cohort studies were analyzed. Survival curves were pooled using a distribution-free random-effects method. RESULTS: Among nine studies, seven (N = 1430 patients) compared the addition of TTFields therapy to standard of care (SOC) chemoradiotherapy versus SOC alone and were included in a pooled analysis for OS. Meta-analysis of comparative studies indicated a significant improvement in OS for patients receiving TTFields and SOC versus SOC alone (HR: 0.63; 95% CI 0.53-0.75; p < 0.001). Among real-world post-approval studies, the pooled median OS was 22.6 months (95% CI 17.6-41.2) for TTFields-treated patients, and 17.4 months (95% CI 14.4-21.6) for those not receiving TTFields. Rates of gross total resection were generally higher in the real-world setting, irrespective of TTFields use. Furthermore, for patients included in studies reporting data on device usage (N = 1015), an average usage rate of ≥ 75% was consistently associated with prolonged survival (p < 0.001). CONCLUSIONS: Meta-analysis of comparative TTFields studies suggests survival may be improved with the addition of TTFields to SOC for patients with newly diagnosed GBM.
Keywords: glioblastom; Real-world; Tumor Treating Fields; Glioblastoma; Brain Neoplasms; Temozolomide; nádory mozku; lidé; Electric Stimulation Therapy; Overall survival; kombinovaná terapie; Combined Modality Therapy; temozolomid; Meta-analysis; TTFields usage; elektrostimulační terapie; Humans